METODE TAGUCHI UNTUK OPTIMALISASI PRODUK PADA RANCANGAN FAKTORIAL - Wuryandari, Triastuti; Widiharih, Tatik; Anggraini, Sayekti Dewi (MEDIA STATISTIKA, 2009)
Taguchi methods represent the effort quality improvement which known as off-line quality control Â method because the method design quality into every appropriate process and product. Taguchi methods is represent quality repair with attempt â€œnewâ€ methods, its meaning do dissimilar approach giving same belief storey by SPC (Statistical Proces Control), very effective in quality improvement as well as lessening expense of same. Fractional factorial design represent base from Taguchi method by fraction from factorial design. Fractional factorial withÂ  4 factors and defining relations p = 2 is or 81 run become or 9 blocks with each blocks there are 9 run just eligible one block. The block name that is Orthogonal Array which lessen time and attemp fare. Orthogonal Array used to device of factorial attemp 3 level by 4 factors that is Orthogonal Array L9. Optimalitation product of factorial design Â can be determinate with tables of anova, table of response and tables of Signal to Noise Ratio. Â  Keywords: Taguchi Methods, Signal to Noise Ratio, Orthogonal Array